Detoxification of Jojoba Meal Simmondsin by Production of Its Protein Isolates as a Protein Source in Food Applications - Ahmed , Dorria M.M.; Mohamed , Rasha K.; Abu-Salem , Ferial M. (International Journal of Halal Research, 2023)
Jojoba meal is a byproduct after oil extraction and serves as an excellent source of protein. Nevertheless, the meal’s presence of toxic factor simmondsin as a cyanogenic glycoside restricted its application and made the researchers seek alternative methods for its detoxification. Jojoba protein isolates were prepared by alkaline extraction at different pHs 8, 9, and 10 (JPI 8, JPI 9, JPI 10) followed by isoelectric precipitation as a procedure for detoxification of jojoba meal from simmondsin and produce safe food-grade functional ingredient (jojoba protein isolate JPI) available to use in many industrial applications. The highest protein yield (83.21%) was recorded in protein isolates extracted at pH 9 (JPI 9) with the highest protein content at 91.15%.Simmondsin content ( mg /kg ) in jojoba meal is 278.79, 5.64 in JPI8, 2.27 in JPI9, and 1.97 in JPI 10. JPI 9 achieved high levels of isoleucine, lysine, cysteine, phenylalanine, tyrosine, and threonine. High chemical protein scores in JPI 9 at 156.98 and 109.01 for threonine, phenylalanine, and tyrosine.The results revealed that JPI9 achieved the highest level and the yield of essential and nonessential amino acids it was used in enriched the biscuit with different levels (5- 10 and 15%) to produce high protein biscuit functional product as one of industrial applications